Analysis of Electronic Channel Service Quality on Customer Satisfaction of Bank Syariah Indonesia (BSI) During the Covid-19 Pandemic - Amora, Ivone Fradia; Supriyanto, Supriyanto (Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
AbstractPurpose - This study aims to examine and analyze how the influence of Electronic Channel (E-Channel) service quality on customer satisfaction of Bank Syariah Indonesia.Method - The research uses a quantitative approach. The population used in this study is the customers of Bank Syariah Indonesia using E-Channel. With the number of samples in this study amounted to 100 respondents.Result - The variables of reliability, privacy and easy to use have a positive and significant effect on customer satisfaction. Meanwhile, the efficiency variable has a negative and significant effect on customer satisfaction. And for the design variable has no effect on customer satisfaction.Implication - The implication is that the quality of e-channel services (electronic channel) provided by the bank will affect customer satisfaction.Originality - This study analyzes the quality of service in the E-Channel includes five components, namely Reliability, Efficiency, Privacy/Security, Design, and Easy to Use on customer satisfaction.